Organisational culture - a fallacy? - Richard D. Lewis (Peoples' Friendship University of Russia (RUDN University), 2021)
In a global economy with such an increase in the role of information technology in global communication more and more national business are forming links with companies in other countries. There is a tendency to expect a degree of uniformity of approach as management behaviours can be argued to express the same aims and broadly similar approaches. However, research shows that although certain concepts may be held in common they are viewed very differently in different cultures perceived and acted upon by managers according to the culture they live and work in. This can lead to disagreements over operations management and communication. Using a two-phase approach this paper explores these cultural differences and their influence on the idea of a common organisational cultures. It argues for a cultural due diligence approach to examining and reconciling potential cultural differences to optimise the international business relationship.